“Obscure Places” in 2 Enoch: What Can They Tell Us about Its Provenance? - Navtanovich, Liudmila (Scrinium, 2022)
2 Enoch is one of the Slavonic pseudepigrapha that has caused and continues to provoke controversy about its origin. In particular, there is no agreement as to whether it comes from Jewish or Christian circles. However, there is a consensus among Slavists on a number of questions concerning its provenance, and these conclusions made by philologists have been confirmed by the Coptic fragments of the text discovered in 2009, and the Slavonic manuscripts themselves give us a lot of information about the possible origin of the text. Among others, the examining of the “obscure places” in 2 Enoch permits us to give an opinion on its possible original, the article deals with the analysis of one of them. At the same time, the research into such readings also demonstrates a long and complicated history of the pseudepigraphon in Slavonic, which we should always have in mind while studying 2 Enoch.